[Rezension von: Zinger, Oded, Living with the law : gender and community among the Jews of medieval Egypt] - Peled, Ilan 1969-; Zinger, Oded (2024)
The volume under review offers a study of the realm of marital disputes among the Jews who lived in Islamic Egypt during the first quarter of the second mi
Keywords: Rezension